Answer:
[tex] \vec{BC}=2b - 4a
[/tex]
[tex] \vec{XY}=a+ b [/tex]
[tex]\vec {CY}=a - 2b[/tex]
Step-by-step explanation:
By the triangular law of vector addition:
[tex]\vec {CY}=\vec {CA}+ \vec{AY}[/tex]
[tex]\vec {CY}=a - 2b[/tex]
We have that;
[tex]\frac{YB}{AY} = \frac{3}{1} [/tex]
[tex] \implies YB = 3 AY \\ \vec {YB} = 3 \vec {AY} [/tex]
[tex]\vec {YB} = 3 a[/tex]
From triangle ABC,
[tex]\vec{BC}=\vec{BA}+\vec{AC}
\\ \vec{BC}=2b - 4a
[/tex]
Again from triangle XYB
[tex]\vec{XY}=\vec{YB}+\vec{BX} \\ [/tex]
[tex]\vec{XY}=\vec{YB}+ \frac{1}{2} \vec{BC}[/tex]
[tex]\vec{XY}=3a+ \frac{1}{2} (2b - 4a)[/tex]
[tex]\vec{XY}=3a+ b - 2a \\ \vec{XY}=a+ b [/tex]